Strategi Nafkah Komunitas Nelayan Dalam Menghadapi Variabilitas Iklim - Salsabila Unaya Bari; Ibnu Phonna Nurdin; Masrizal Masrizal (Jurnal Masyarakat Maritim, 2024)
Coastal communities face challenges in carrying out their fishing activities due to climate variability. The negative impacts of climate variability hinder fishing communities from carrying out their daily routines. This research aims to provide a description of the fishing community's exposure to climate variability and analyze the forms of livelihood strategies implemented by the fishing community in dealing with climate variability. This research was conducted in the coastal area, precisely in Gampong Lhok Lamteungoh, Peukan Bada District, Aceh Besar Regency. Data collection was carried out through direct interviews and observations in the area where the fishing community lived, which was selected using purposive sampling. The research results showed that serious impacts were found due to climate variability on the fishing community in Gampong Lhok Lamteungoh, including: high rainfall, exposure to extreme winds, uncertain fishing seasons and vulnerable settlements due to being prone to flooding. Several forms of climate variability are detrimental to fishing communities in carrying out their activities. Therefore, in order for the fishing community to be able to maintain its existence, several forms of livelihood strategies are needed. The fishing community has developed several forms of livelihood strategies that are developed within the community, namely: intensification and extensification, livelihood diversification, and migration.  The research results show that developing this livelihood strategy is an alternative solution for fishing communities facing climate variability. It is hoped that the government can provide assistance and solutions for fishing communities, especially when climate variability hits them.